Biological Activity of a Coumarin Derivative on Heart Failure Using an Ischemia/Reperfusion Injury Model - Figueroa-Valverde, Lauro; Rosas-Nexticapa, Marcela; Alvarez-Ramirez, Magdalena; Melgarejo-Gutiérrez, Montserrat; Mateu-Armand, Virginia; Garcimarrero-Espino, Alejandra (Drug Research, 2024)
Heart failure is a health problem worldwide. There are some drugs for it, including digoxin, spironolactone, captopril, and valsartan, but some of these drugs can produce secondary effects, such as arrhythmia, cough, hyperkalemia, hyponatremia and hypotension. The aim of this research was to evaluate the biological activity of coumarin (2H-chromen-2-one) and its derivatives (3BrAcet-C, 3–4Br-Ph-C, 4-CN-7D-C, 4-Me-7-Ph-C and 6Br-3-D-C) against ischemia/reperfusion injury as a therapeutic alternative for heart failure. In addition, the biological activity of the coumarin derivative 4-Me-7-Ph-C on left ventricular pressure (LVP) was determined in the absence or presence of ouabain and nifedipine at a dose of 1 nM using an isolated rat heart model. The results showed that i) the coumarin derivative 4-Me-7-Ph-C significantly decreased the infarct area (p+=+0.05) compared with 3BrAcet-C, 3–4Br-Ph-C, 4-CN-7D-C, and 6Br-3-D-C; and ii) 4-Me-7-Ph-C increased LVP in a dose-dependent manner, which effect was inhibited by nifedipine. These data suggest that coumarin 4-Me-7-Ph-C may act as a type-L calcium channel activator, so it could be a good agent to treat heart failure.
Keywords: coumarin; heart failure; calcium channel